Dance in tourism from an anthropological perspective: An introduction to the research issue - Banio, Adrianna; Malchrowicz-Mośko, Ewa (Turyzm/Tourism, 2019)
Nowadays, dance plays an important role in the modern tourism industry. Today, the craze for dancing creates great opportunities for cultural tourism. However, it should be remembered that there is a great danger of losing the most important meaning of dance by commercializing and reducing its essence. Dance tourism as discussed in the article is understood as travel for the purpose of learning about dance and its culture in places where given dance styles were born, or where they play an important national role as well as enjoying great popularity among the local community. This article is an introduction to the issue of dance tourism in an anthropological context. It presents potential attractions related to dance in the perspectives of cultural and sports tourism, it has an illustrative and descriptive character while its method is a literature review and presentation of popular examples.